Manajemen Pemasaran Sekolah Menengah Kejuruan Islamic Center Cirebon Dalam Membangun Brand Image Untuk Meningkatkan Minat Calon Peserta Didik - Asep - Kurniawan (LP2M IAIN Syekh Nurjati Cirebon, 2022)
Educational Institution manages education marketing properly in order to attract consumer interest. The aim of this research was to determine education marketing management in building a brand image to increase the interest of prospective students in Vocational Schools Islamic Center Cirebon. The method used in this research was descriptive qualitative method. Data collection techniques were in-depth interviews, in-depth observations and documentation studies. The data analysis techniques were data collection, data reduction, data presentation and data conclusions. It shown that the school implemented a process of planning, implementing, and supervising the school's marketing. In addition, schools also implemented supporting factors and minimized obstacles in building a brand image so that it could attract students' interest.